Composite material identification using a two-stage meta-heuristic hybrid approach incorporated with a two-level FRF selection scheme - Tam, Jun Hui; Ong, Zhi Chao; Ho, Kye Wenn (Elsevier, 2019)
A different identification method for isotropic and composite materials, known as, the two-stage meta-heuristic hybrid GA-ACO-PSO optimization method which involves the use of the natural frequency error function in the first stage, followed by the use of the frequency response function (FRF) error function in the second stage, has been proposed. A two-stage approach is suggested along with a two-level FRF selection scheme to mitigate the effects due to uncertainties as well as to improve the identifiability of the in-plane shear modulus and Poisson's ratio. The emphasis is placed on the implementation of the two-level FRF selection scheme on account of its pivotal role in ensuring more accurate outcomes. A discernible reduction can be observed in the absolute percentage errors of the in-plane shear modulus and Poisson's ratio from the first to second stages of identification, which consequently, acknowledges the feasibility of the proposed approach in improving the identifiability of the aforementioned parameters. As compared with conventional destructive methods, the proposed method can be technically useful for industrial applications, especially in the manufacturing industry and construction industry, where operational time and cost are the primary concerns. © 2019 Elsevier Ltd